Answer:
Explanation:
1). Given equation is,
2x² - 3x = 6
2x² - 3x - 6 = 0
To find the solutions of the equation we will use quadratic formula,
x =
![(-b\pm√(b^2-4ac))/(2a)](https://img.qammunity.org/2022/formulas/mathematics/college/u78krxfapax436gdy3cmzl9tlxme7ejm5h.png)
Substitute the values of a, b and c in the formula,
a = 2, b = -3 and c = -6
x =
![(3\pm√((-3)^2-4(2)(-6)))/(2(2))](https://img.qammunity.org/2022/formulas/mathematics/college/qx86l9awau3kl3940sjnajdnyv1vranlue.png)
x =
![(3\pm√(9+48))/(4)](https://img.qammunity.org/2022/formulas/mathematics/college/r8yti4mp4qmegt0lpc17y36xs3xu6z9jp7.png)
x =
![(3\pm√(57))/(4)](https://img.qammunity.org/2022/formulas/mathematics/college/kaxa0e7eoxtx8a2hh24mgol3ynr5eqey3f.png)
x =
![(3+√(57))/(4),(3-√(57))/(4)](https://img.qammunity.org/2022/formulas/mathematics/college/wawywhx0t2qy0g0ya3ek38r5ybo9e4hmsf.png)
Therefore, there are two real solutions.
2). Given equation is,
x² + 1 = 2x
x² - 2x + 1 = 0
(x - 1)² = 0
x = 1
Therefore, there is one real solution of the equation.
3). 2x² + 3x + 2 = 0
By applying quadratic formula,
x =
![(-b\pm√(b^2-4ac))/(2a)](https://img.qammunity.org/2022/formulas/mathematics/college/u78krxfapax436gdy3cmzl9tlxme7ejm5h.png)
x =
![(-3\pm√(3^2-4(2)(2)))/(2(2))](https://img.qammunity.org/2022/formulas/mathematics/college/ytoe2tyly0t7vdlb52c74bb9526lnmwdq1.png)
x =
![(-3\pm√(9-16))/(4)](https://img.qammunity.org/2022/formulas/mathematics/college/jtbiqtihb3v48q9e31zm3bmg82pj2i2gce.png)
x =
![(-3\pm i√(7))/(4)](https://img.qammunity.org/2022/formulas/mathematics/college/ddbk0dp69m6f75c1d4mxyfquocbon8c6ru.png)
x =
![(-3+ i√(7))/(4),(-3- i√(7))/(4)](https://img.qammunity.org/2022/formulas/mathematics/college/62jv5611civk6zqt4fd2haalyx4ds8cai0.png)
Therefore, there are two complex (non real) solutions.